Analisis Tahap Kedukaan yang Dialami oleh Tokoh Yusuke Kafuku dan Misaki Watari dalam Film Drive My Car Karya Ryusuke Hamaguchi (Kajian Psikologi Sastra) - Wulandari, Dyan; Lestari, Dwi Astuti Retno; Fredy, Mochammad (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2025)
This study analyzes the stages of grief experienced by Yusuke Kafuku and Misaki Watari in the film Drive My Car. The purpose of this study is to describe the stages of grief experienced by Kafuku and Watari, as well as to identify the factors that differentiate the stages of grief experienced by the two. The theories used in this study are the five stages of grief theory and mise en scène as a supporting framework for analyzing the cinematic elements of the film in depicting the characters' emotions. The method used in this study is qualitative, as the data collected comes from a film consisting of words, sentences, and images. The results of this study found that Yusuke Kafuku experienced all stages of grief but in a non-linear pattern. The stages he went through included denial, anger and depression, which overlapped, bargaining, and acceptance. On the other hand, Misaki Watari only went through two stages of grief, namely depression and acceptance.